A permittivity-conductivity joint model for hydrate saturation quantification in clayey sediments based on measurements of time domain reflectometry - Xing, Lanchang; Gao, Liang; Ma, Zisheng; Lao, Liyun; Wei, Wei; Han, Weifeng; Wang, Bin; Gao, Muzhi; Xing, Donghui; Ge, Xinmin (Elsevier, 2024)
Hydrate saturation (Sh) is one of the key parameters for resource assessment of hydrate reservoirs and production optimization of natural gas. There are still significant challenges in determining the Sh in clayey formations. Both dielectric and resistivity logging tools have been used for identifying and evaluating hydrate-bearing formations; however, there is little work on a joint analysis and modelling of the permittivity and resistivity for quantifying the Sh. To bridge the knowledge gap, we have proposed a novel permittivity-conductivity (P–C) joint approach based on TDR (time domain reflectometry)-derived parameters (i.e., apparent permittivity Ka and bulk conductivity σdc) in this work. The proposed P–C joint approach can provide a theoretical basis for the joint interpretation of dielectric and resistivity geophysical measurements on hydrate-bearing formations in the field. First, the basic theory for deriving the Ka and σdc from the TDR responses of hydrate-bearing sediments was formulated based on the dielectric polarization and electrical conduction mechanisms. Second, an experimental campaign was carried out including the development of experimental system, calibration of TDR probe and design of experimental scheme. Third, the influences of hydrate saturation, clay mineralogy and clay content on the TDR responses of unconsolidated sediments were examined. Then the Ka and σdc were related to Sh respectively, and finally a novel P–C joint model for the quantification of Sh in clayey sediments was established and verified. It has been demonstrated that: (1) the Ka of the clayey samples with hydrates decreases almost linearly with an increasing clay content up to 20 %, while the σdc of the smectite-bearing samples decreases nonlinearly in contrast to the linear trend for illite; (2) the power-law mixing formula incorporating an empirical exponent is a preferable permittivity model for hydrate-bearing clayey sediments due to its merits of empirical and theoretical nature, while the Simandoux equation is effective to account for the clay effects on the conductivity of hydrate-bearing sediments with smectite and illite; (3) the P–C joint model can be established by utilizing the porosity of hydrate-bearing sediments as a bridge parameter between Ka and σdc. The variation behavior of Ka and σdc with different types and contents of clay minerals can be explained by the difference of the amount of bound water and swelling effects between the illite-bearing and smectite-bearing samples. The proposed P–C joint model outperforms the standalone permittivity-based and conductivity-based models especially for the clayey cases. The root-mean-squared errors of the P–C joint models are 7.339, 2.930 and 2.065 % for the clean-sand samples, clayey samples with illite and smectite, respectively.
Keywords: gas hydrate; time domain reflectometry; hydrate saturation; Dielectric permittivity; Conductivity; Joint approach